Racism in Argentine Higher Education: Proposals for an Inclusive Foreign Language Teacher Training - Ferrara, Candelaria (2023)
In Latin America, racism has been a problem since colonial times and is still found in higher education discriminatory practices. Contemporary racism in teacher training institutions and in foreign language career proposals is characterized by the lack of diversity in many aspects such as institutional human landscape, bibliography, language, and cultural uses. All this maintains a higher education that has traditionally produced and still produces a social reality that is non-plural, inequitable, unjust, and in need of revision. This omission of plurality needs to include strategies that link the field of higher education and excluded social groups. To this end, we suggest that service-learning could contribute to an inclusive training of foreign language teachers in an Ecology of Knowledge with other possible and necessary knowledges, ways, voices of diverse groups, so necessary for a non-racist higher education. We believe that overcoming the idea of the individual and alluding to the community, going beyond the doors of the institutions in an exchange of knowledge through practical interventions in the community beyond academicism is a practice that deserves to be further developed in higher education institutions. We propose lines of work to carry out a process of change in our teacher training programs and spaces for the construction of a better society. Service-learning is a feasible path that implies an anti-racist stance and we, the higher education community, have the imagination and qualifications required to generate and undertake this transgressive task of a collaborative and plural construction for a diverse, equitable, and just social reality.